Study of the response of an ORTEC GMX45 HPGe detector with a multi-radionuclide volume source using Monte Carlo simulations. (July 2016) - Saraiva, A.; Oliveira, C.; Reis, M.; Portugal, L.; Paiva, I.; Cruz, C.
Abstract: A model of an n-type ORTEC GMX45 HPGe detector was created using the MCNPX and the MCNP-CP codes. In order to validate the model, experimental efficiency was compared with the Monte Carlo simulations results. The reference source is a NIST traceable multi-gamma volume source in a water-equivalent epoxy resin matrix (1.15 g cm −3 density) containing several radionuclides: 210 Pb, 241 Am, 137 Cs and 60 Co in a cylinder shape container. Two distances of source bottom to end cap front surface of the detector have been considered. The efficiency for the nearest distance is higher than for longer distance. The relative difference between the measured and the simulated full-energy peak efficiency is less than 4.0% except for the 46.5 keV energy peak of 210 Pb for the longer distance (6.5%) allowing to consider the model validated. In the absence of adequate standard calibration sources, efficiency and efficiency transfer factors for geometry deviations and matrix effects can be accurately computed by using Monte Carlo methods even if true coincidence could occur as is the case when the 60 Co radioisotope is present in the source. Highlights: High resolution gamma-ray spectrometry. Computation of efficiencies by using Monte Carlo methods. Use of traceable multi-gamma volume sources to validate the MC model. Enabling the calculations of true coincidence summing effects and efficiency transfer factors for geometry deviations.